1998
DOI: 10.1021/jf980128o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Most Potent Odorants in Wild and Farmed Cooked Turbot (Scophtalamus maximusL.)

Abstract: Potent odorants of wild and farmed turbot (Scophtalamus maximus L.) were investigated by an olfactometry global method to point out odorant detection frequency and by aroma extract dilution analysis (AEDA). Thirty-four compounds were detected and 24 identified. Among these compounds, trimethylamine (fishy), 2,3-butanedione (buttery), (Z)-4-heptenal (potato-like), 4-methyl-2-pentanol (mushroom-like), (E,Z)-2,6-nonadienal (cucumber-like), and (E,E)-2,4-decadienal (cucumber-like) showed a high detection frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…It is nevertheless true that some volatile compounds from lipid oxidation, like (Z)-4-heptenal and hexanal (Prost et al 1998), above odour threshold, could be responsible for off-flavours and consequently can deteriorate the organoleptic profile of cooked fillets.…”
Section: Cookingmentioning
confidence: 99%
“…It is nevertheless true that some volatile compounds from lipid oxidation, like (Z)-4-heptenal and hexanal (Prost et al 1998), above odour threshold, could be responsible for off-flavours and consequently can deteriorate the organoleptic profile of cooked fillets.…”
Section: Cookingmentioning
confidence: 99%
“…This compound has been previously reported as one of the most odorous in mussels 36 and clams. 37 Prost et al 23 showed that (E)-2-penten-1-ol contributed partially to the aroma of farmed turbot. (E)-2-Hexen-1-ol was perceived by six, seven and six judges in extracts of ®sh fed FO, SO and LO diets respectively and exhibits a green and moss-like odour.…”
Section: Olfactometry Analysismentioning
confidence: 99%
“…20±22 Prost et al, 23 using olfactometric methods, have shown that the main odouractive compounds in muscle of wild and farmed turbot resulted from oxidation of PUFA. The aim of the present study was to determine the effects of experimental diets containing ®sh oil, soybean oil or linseed oil on odour-active compounds of turbot¯esh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other saturated aliphatic aldehydes such as octanal and decanal have grassy and oily odors. Ketones, which are derived from PUFA oxidative degradation [22], have a higher threshold value compared to aldehydes and a relative small contribution to fish aroma [23,24]. However, the flavor differences among fish were mainly attributed to carbonyl compounds, so ketones have certain influences on flavor development [25].…”
Section: Volatile Compounds In Four Steamed Coilia Ectenesmentioning
confidence: 99%